But in the End, Why is Deleuze “Anti-Hegelian”? At the Root of the Hegel–Deleuze Affair - Pezzano, Giacomo (Religija ir kultūra, 2014)
Deleuze said that he detested Hegelianism and dialectics: this paper claims that Deleuze is contra Hegel because he has and proposes a different philosophical system. Thus, I suggest that if we want to understand the reason of such a “disgust,” we need to focus the philosophical question that moves the entire Deleuzian system (§ 1). Then, I explain that if the ground-question of Hegel’s philosophy is “how is it possible that things are surpassed, that they go on?”, the Deleuzian one is “how is it that there is always something new, that things come out?” (§ 2). Finally, I discuss how desire can be considered as a key-example for seeing how the perspectives of the two thinkers diverge (§ 3).